2020
DOI: 10.3390/molecules25245884
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Mercury Ingestion from Canned Fish in Poland

Abstract: In this study, total mercury content was determined in 84 canned fish corresponding to commonly consumed brands (over 14 different producers), which were purchased from local markets in Poland in the years 2019–2020. For comparison purposes, samples of both the matrix in which the fish were kept along with the seafood samples were measured. The analyses were carried out using the cold vapor AAS technique. Statistical analyses were employed to identify significant differences in mercury content in relation to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
3
0
1
Order By: Relevance
“…These authors argued that the high variability in metal concentrations may have been responsible for the lack of differences. In a study with canned tuna in oil matrices, salads, sauces, and pastes, no statistically significant differences were found among presentations, and it was concluded that Hg content was not affected by the packaging medium (Pawlaczyk et al 2020). High variability in metal content among canned fisheries products makes it difficult to establish patterns of Hg accumulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These authors argued that the high variability in metal concentrations may have been responsible for the lack of differences. In a study with canned tuna in oil matrices, salads, sauces, and pastes, no statistically significant differences were found among presentations, and it was concluded that Hg content was not affected by the packaging medium (Pawlaczyk et al 2020). High variability in metal content among canned fisheries products makes it difficult to establish patterns of Hg accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…Copyediting by MacTavish Scientific Editing. diferencias significativas entre las diferentes presentaciones y se concluyó que el contenido de Hg no se ve afectado por el medio en el cual se enlata (Pawlaczyk et al 2020). La elevada variabilidad en el contenido de metales en los moluscos enlatados dificulta el establecimiento de patrones de acumulación de Hg.…”
Section: Discussionunclassified
“…Also, mercury has been suspected to be part of ALS pathogenesis [ 136 ], but results are inconclusive, especially regarding mercury exposure from diet, and in particular seafood consumption [ 137 ]. Mercury is produced by several industries and stores in aquatic predatory organisms such as shark, swordfish, mackerel and tuna [ 138 ]. Mercury can generate oxygen free radicals, promote excitotoxicity, and decrease DNA, RNA and protein synthesis, [ 139 ], all processes that have been associated with ALS [ 140 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, these differences may be attributed to the difference in fish species and fishing areas. Fish caught in the Atlantic Ocean presented higher mercury content than the ones from closed seas (Pawlaczyk et al, 2020). In addition, T-Hg concentrations might also be affected by the size/age of the fish species (Wei et al, 2018).…”
Section: Fish Contamination Levelsmentioning
confidence: 94%